2002
DOI: 10.1086/339402
|View full text |Cite
|
Sign up to set email alerts
|

Solar Phenomena Associated with “EIT Waves”

Abstract: In an effort to understand what an '' EIT wave '' is and what its causes are, we have looked for correlations between the initiation of EIT waves and the occurrence of other solar phenomena. An EIT wave is a coronal disturbance, typically appearing as a diffuse brightening propagating across the Sun. A catalog of EIT waves, covering the period from 1997 March through 1998 June, was used in this study. For each EIT wave, the catalog gives the heliographic location and a rating for each wave, where the rating is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
244
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(260 citation statements)
references
References 22 publications
13
244
1
2
Order By: Relevance
“…A recent study by Nitta et al (2013) found a higher association of AIA waves with type II bursts, namely 54%. This higher percentage could be due to a selection effect, since the AIA wave sample did not include slow and weak disturbances that are part of the EIT wave catalog used by Biesecker et al (2002). This is consistent with the finding that the median speed of AIA waves without type II bursts was somewhat lower than the speed of the burst-associated waves (550 versus 650 km s -1 ).…”
Section: Metric Type II Radio Burstssupporting
confidence: 77%
See 2 more Smart Citations
“…A recent study by Nitta et al (2013) found a higher association of AIA waves with type II bursts, namely 54%. This higher percentage could be due to a selection effect, since the AIA wave sample did not include slow and weak disturbances that are part of the EIT wave catalog used by Biesecker et al (2002). This is consistent with the finding that the median speed of AIA waves without type II bursts was somewhat lower than the speed of the burst-associated waves (550 versus 650 km s -1 ).…”
Section: Metric Type II Radio Burstssupporting
confidence: 77%
“…The converse is not true, since only 21% of EIT waves are accompanied by type II bursts (Biesecker et al, 2002). A recent study by Nitta et al (2013) found a higher association of AIA waves with type II bursts, namely 54%.…”
Section: Metric Type II Radio Burstsmentioning
confidence: 95%
See 1 more Smart Citation
“…Following Chen & Fang (2012), we use "EIT waves" for the slower type of EUV waves specifically. Biesecker et al (2002) did a statistical study of EIT waves observed by SOHO/EIT (195 Å) telescope and found that some of the EIT waves have sharp, bright features, which they called "S-waves." These S-waves may be the signature of Moreton waves.…”
Section: Introductionmentioning
confidence: 99%
“…Such large-scale events as EIT wave connect to flares or CME (e.g. Chertok & Grechnev (2003), Biesecker et al (2002), Wills-Davey et al (2007)). …”
Section: Introductionmentioning
confidence: 99%